A Study of Courier Service Quality and Customer Satisfaction - Rui Qi Tang; Ying Jie Tan; Zhi Xuan Tan; Yean Ting Tan; Ghezlan Almawad; Asla Alosaimi (International Journal of Applied Business and International Management, 2022)
Courier services have grown in popularity due to the recent Covid-19 outbreak. We aim to examine how courier service quality dimensions such as tangibility, reliability, responsiveness, assurance, and empathy can affect customer satisfaction. We conducted an online survey with 159 participants from Malaysia and Kuwait. We found that reliability, responsiveness, and empathy are significantly related to customer satisfaction. Furthermore, we identified that empathy is the most significant factor influencing customer satisfaction. Our study contributes to the prior research on customer satisfaction by showing that service quality dimensions play an important role in influencing customer satisfaction.